산 처리와 pH 조절을 이용한 사문석군 광물로부터 규소와 철산화물 회수 및 광물 탄산화 연구 - 백지연(Jiyeon Baek); 조연우(Yeonu Jo); 이정헌(Jeongheon Lee); 권나윤(Nayoon Kwon); 김예람(Yeram Kim); 최숙(Suk Choi); 김성희(Sunghee Kim); 노열(Yul Roh) (자원환경지질, 2016)
The objectives of this study were to recover silica and iron oxides and $CO_2$ sequestration using serpentine via various acid dissolution and pH swing processes. Serpentine collected from Guhang-myeon in S. Korea were mainly composed of antigorite and magnetite consisting of $SiO_2$ (45.3 wt.%), MgO (41.3 wt.%), $Fe_2O_3$ (12.2 wt.%). Serpentine pulverized ($${\leq_-}75{\mu}m$$) and then dissolved in 3 different acids, HCl, $H_2SO_4$, $HNO_3$. Residues treated with acidic solution were recovered from the solution (step 1). And then the residual solution containing dissolved serpentine was titrated using $NH_4OH$. And pH of the solution increased up to pH=8.6 to obtain reddish precipitates (step 2). After recovery of the precipitates, the residual solution reacted with $CO_2$ and then pH increased up to pH=9.5 to precipitate white materials (step 3). The mineralogical characteristics of the original sample and harvested precipitates were examined by XRD, and TEM-EDS analyses. ICP-AES analysis was also used to investigate solution chemistry. The dissolved ions were Mg, Si, and Fe. The antigorite became noncrystralline silica after acid treatment (step 1). The precipitate at pH=8.6 was mainly amorphous iron oxide, of which size ranged from 2 to 10 nm and mainly consisting of Fe, O, and Si (step 2). At pH=9.5, nesquehonite [$Mg(HCO_3)(OH){\cdot}2(H_2O)$] and lasfordite [$MgCO_3{\cdot}H_2O$] were formed after reaction with $CO_2$ (step 3). The size of carbonated minerals was ranged from 1 to $6{\mu}m$. These results indicated that the acid treatment of serpentine and pH swing processes for the serpentine can be used for synthesis of other materials such as silica, iron oxides and magnesium carbonate. Also, This process may be useful for the precursor synthesis and $CO_2$ sequestration via mineral carbonation. 이 연구는 사문석군 광물을 산 처리하고, 용출액을 pH 조절 하여 사문석군 광물로부터 규소와 철산화물 회수와 광물탄산화에 대해 연구하고자 하였다. 연구에 사용된 암석시료는 홍성 구항면에서 채취한 사문암으로 안티고라이트와 자철석로 구성되며, $SiO_2$(45.3 wt.%), MgO(41.3 wt.%), $Fe_2O_3$(12.2 wt.%)의 화학조성을 보였다. 자원회수실험은 $75{\mu}m$ 이하의 크기로 분쇄한 사문암을 1 M의 염산, 황산, 질산으로 각각 용해시켜 잔류물을 추출(1 단계)하였고, 남은 용출액에 $NH_4OH$를 추가하여 pH=8.6까지 상승시켜 형성된 붉은색 침전물을 회수(2 단계)하였다. 광물탄산화 실험은 침전물이 제거된 상층액에 $CO_2$를 주입한 후, pH=9.5까지 상승시켜 형성된 백색의 침전물을 회수(3 단계)하였다. 각 단계에서 회수된 잔류물과 침전물의 광물학적 특성을 확인하기 위해 XRD, TEM-EDS 분석을 실시했고, 용출액과 침전물이 제거된 상층액에 함유된 원소(Si, Mg, Fe)의 농도 변화는 ICP-AES 분석을 통해 확인했다. 용출된 금속은 Si, Fe, Mg이었다. 안티고라이트는 산과 반응한 후에도 판상을 유지하나 비정질실리카로 변했다(1 단계). pH=8.6에서 회수된 침전물은 Fe, Si, O로 구성된 비정질광물로, 2~10 nm 크기의 구형 나노물질이었다(2 단계). 마지막으로 $CO_2$를 주입한 후, pH=9.5에서 회수된 침전물은 nesquehonite[$Mg(HCO_3)(OH){\cdot}2(H_2O)$]와 lansfordite[$MgCO_3{\cdot}H_2O$]로 $1{\sim}6{\mu}m$ 크기를 가진 주상의 결정질광물이었다(3 단계). 따라서 산 처리된 사문석군 광물에서 나노물질의 실리카(잔류물)과 철산화물(침전물)을 회수가능하며, $CO_2$ 반응과 pH 조절을 이용하여 탄산염광물을 형성하였다. 회수된 실리카와 철산화물은 다른 물질로 합성하는 전구체로 유용하게 이용될 수 있으며, 이산화탄소를 이용한 광물탄산화 반응은 대기 중 이산화탄소 고정에 응용될 수 있을 것으로 기대된다.